Improvement of Mathematics Learning Results Through Active Learning Model Type of Index Card Match (ICM) - Rusmini Rusmini (Universitas Sebelas Maret, 2020)
This study aims to determine the increase in cognitive and affective learning outcomes of Mathematics and the learning process of Class IV students in Semester I of SD Negeri 2 Paranggupito for the Academic Year 2019/2020. This research is a classroom action research with 10 students in Class IV Semester I SD Negeri 2 Paranggupito Academic Year 2019/2020 as the subject. The research was conducted in two cycles, two meetings per cycle. Data collection by tests and observations. The analysis uses quantitative and qualitative. The results showed that there was an increase in Mathematics learning outcomes after using Active Learning type Index Card Match according to the Cycle I syntax. The increase again occurred after being modified with discussion, rewards, and the addition of Cycle II quiz rules. Cognitive value from 68.70 in Pre-cycle to 86.93 Cycle II. The affective aspect increased from 2.47 (good) Cycle I to 3.04 (good) Cycle II. The application of the Index Card Match Type Active Learning model until Cycle II obtained data > 75% of all students scored ≥ 70.